Microbial Biocontrol Strategies for Ambrosia Beetles and Their Associated Phytopathogenic Fungi - Reverchon, Frédérique; Contreras-Ramos, Silvia M.; Eskalen, Akif; Guerrero-Analco, José A.; Quiñones-Aguilar, Evangelina E.; Rios-Velasco, Claudio; Velázquez-Fernández, Jesús B. (Frontiers in Sustainable Food Systems, 2021)
Ambrosia beetles and their symbiotic fungi are causing severe damage in natural and agro-ecosystems worldwide, threatening the productivity of several important tree crops such as avocado. Strategies aiming at mitigating their impact include the application of broad-spectrum agrochemicals and the incineration of diseased trees, but the increasing demand for environment-friendly strategies call for exploring biological control for the management of ambrosia beetles and their phytopathogenic fungal symbionts. The aim of this review is to examine the existing knowledge on biocontrol approaches using beneficial microorganisms and microbial natural products with entomopathogenic and antifungal activity against ambrosia beetles and fungi. We show that biocontrol has been mainly focused on the insect, using entomopathogenic fungi (EPF) such as Beauveria spp. or Metarhizium spp. However, recent studies have been integrating EPF with mycoparasitic fungi such as Trichoderma spp. to simultaneously challenge the vector and its fungal symbionts. Novel approaches also include the use of microbial natural products as insect lures or antifungal agents. Contrastingly, the potential of bacteria, including actinobacteria (actinomycetes), as biocontrol agents of ambrosia fungi has been little investigated. We thus suggest that future research should further examine the antifungal activity of bacterial strains, with an emphasis on harsh environments. We also suggest pursuing the isolation of more effective microbial strains with dual biocontrol effect, i.e. exhibiting fungicidal/insecticidal activities. Moreover, additional efforts should aim at determining the best application methods of biocontrol agents in the field to ensure that the positive effects detected in vitro are sustained. Finally, we propose the integration of microbiome studies in pest and disease management strategies as they could provide us with tools to steer the beneficial host plant microbiome and to manipulate the beetle microbiome in order to reduce insect fitness.